The language of fatalism in the lyrical proposition of the Ecuadorian corridors - Núñez Torres, María Giovanna (2022)
The Ecuadorian corridor as an expression of feeling, bitterness, and emotional relief, generally always contains a greater or lesser degree of fatalism in its design and structure, mainly due to a clear purpose of exalting the cultural values of the Ecuadorian people, especially in what it concerns the national spirit and the reactions of the defined idiosyncrasy typical of this country. The objective of this research was to identify the presence of fatalistic language expressed in the lyrics of some Ecuadorian corridors to identify possible patterns in its use. The research was also based on the Interpretative Hermeneutical research paradigm of qualitative methodology with a documentary-type research process, where commercial literature such as songbooks and magnetic acetate discs whose level of dissemination is public was analyzed. This information collected was cataloged, reaching the conclusion that the representation of evident fatalism in the belief in a superior force, feelings of frustration and misery, rebellion in the face of reality, paradoxical resignation, obsession with pain, boredom, and melancholy concur and evasion through the ingestion of liquor or some hallucinogen, which are present in the behavioral traits and idiosyncrasy of the Ecuadorian people.